Length time bias in surveillance for hepatocellular carcinoma and how to avoid it. Issue 12 (30th March 2016) - Cucchetti, Alessandro; Garuti, Francesca; Pinna, Antonio Daniele; Trevisani, Franco; ,
Abstract : Aim: Length time bias is a selection bias which can lead to an overestimation of survival of screening‐detected cases caused by the relative excess of slower‐growing tumors detected with respect to symptomatic cases. This leads to the incorrect perception that screening improves outcomes when it only selects tumors with a favorable biology. Data regarding this bias in surveillance for hepatocellular carcinoma (HCC) have never been provided. Methods: A semi‐Markov model was developed to investigate this issue. An exponential tumor growth was applied. During its growth, tumor diagnosis "at surveillance appointments" was made when tumor attained a size equal to or above the size of tumors diagnosed in surveilled patients obtained from pertinent published reports, or "in‐between appointments" (due to the development of symptoms) if tumor size attained the size of symptomatic diagnosis, derived from published reports; otherwise the tumor continued to grow until the time horizon had been reached. Tumor doubling time (DT) values were recorded according to the method of diagnosis. Results: In a theoretical cohort of 1000 patients submitted to semiannual surveillance, 72.5% will be diagnosed at a surveillance appointment and 18% because of symptom development, although under surveillance. Patients diagnosed with HCC at a surveillance appointment had a median tumor DT of 100 days (interquartile range, 68–143 days), whereas those diagnosed because of symptoms had a median DT of 42 days (interquartile range, 29–58 days) although under surveillance. Conclusion: The surveillance propensity to detect slower‐growth tumors is relevant, and practical suggestions to minimize this bias in longitudinal studies are provided.